A new species of Tropidion (Neoibidionini), synonymies in Rhinotragini, notes on Pirangoclytus (Clytini) and Hemicladus (Calliini), and new records in Cerambycidae (Coleoptera) - Santos-Silva, Antonio; Nascimento, Francisco E. De L.; Biffi, Gabriel (Zootaxa, 2019)
A new species, Tropidion flechtmanni, is described, illustrated, and included in a previous key. Rhinotragus marginatus Perty, 1832 (currently considered a subspecies of R. dorsiger), Rhinotragus dorsiger var. collaris Melzer, 1930, Rhinotragus dorsiger var. vittatus Melzer, 1930, Rhinotragus dorsiger var. amparensis Melzer, 1930, and Rhinotragus apicalis Guérin-Méneville, 1844 are formally synonymized with R. dorsiger Germar, 1823. Variation in pubescence pattern in Pirangoclytus purus (Bates, 1870) is reported, and the species is recorded for the first time in the Brazilian state of Mato Grosso do Sul. Variation in the color of the integument and pubescence in Hemicladus thomsonii Buquet, 1857 is reported, and the species is recorded for the Brazilian states of Mato Grosso do Sul, Rio de Janeiro and São Paulo. New state records are provided for Amorupi fulvoterminata (Berg, 1889), Eclipta vitticollis (Bates, 1873), Steirastoma stellio Pascoe, 1866, Cicuiara nitidula (Bates, 1866), Hesycha inermicollis (Breuning, 1940), and Polyrhaphis gracilis Bates, 1862.